Hemangioma of the face and neck with phleboliths: Diagnostic imaging with X-ray and CT - Valerio, Claudia Scigliano; Xambre, Pedro Augusto Oliveira Santos; Vidigal, Bruno César Ladeira; Rocha, Beatriz de Carvalho Silva; Manzi, Flávio Ricardo (Journal of Oral Diagnosis, 2017)
Hemangiomas found in the head and neck regions can cause functional and aesthetic complications. The therapeutic approach to this condition presents both challenges and risks, mainly when surgical procedures must be performed due to the risk of hemorrhaging. In this context, the need for tooth extraction can represent a factor of great concern. The present study describes the case of extensive cavernous hemangioma, associated with a large quantity of phleboliths, affecting the orofacial and neck region in an adult woman. Embolization and controls were performed as a means of surgical treatment.